2013
DOI: 10.1093/nar/gkt1093
|View full text |Cite
|
Sign up to set email alerts
|

CPLM: a database of protein lysine modifications

Abstract: We reported an integrated database of Compendium of Protein Lysine Modifications (CPLM; http://cplm.biocuckoo.org) for protein lysine modifications (PLMs), which occur at active ε-amino groups of specific lysine residues in proteins and are critical for orchestrating various biological processes. The CPLM database was updated from our previously developed database of Compendium of Protein Lysine Acetylation (CPLA), which contained 7151 lysine acetylation sites in 3311 proteins. Here, we manually collected expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 40 publications
2
112
0
2
Order By: Relevance
“…In Mus musculus , the focus of the majority of acetyl-proteomics studies, 13,186 sites across 4,024 proteins have been identified and a full 63% of mitochondrially localized proteins contain acetylation sites. A comparable amount of sites have been found in human cell lines: ~11,000 sites [4446]. The bulk of this data has been generated in the past four years.…”
Section: Probing the Extent Of The Mitochondrial Acetylomementioning
confidence: 85%
“…In Mus musculus , the focus of the majority of acetyl-proteomics studies, 13,186 sites across 4,024 proteins have been identified and a full 63% of mitochondrially localized proteins contain acetylation sites. A comparable amount of sites have been found in human cell lines: ~11,000 sites [4446]. The bulk of this data has been generated in the past four years.…”
Section: Probing the Extent Of The Mitochondrial Acetylomementioning
confidence: 85%
“…For instance, an integrated database of Compendium of Protein Lysine Modifications reported that there are 7151 lysine acetylation sites in 3311 proteins (Liu et al, 2014). This is supported by experimentally that CBP/p300, PCAF, and HDACs have non-histone target proteins, such as transcription factors, transcription cofactors, and cytoskeleton (Brochier et al, 2013; Chen et al, 2005; Dompierre et al, 2007; Federman et al, 2013; Gaub et al, 2010).…”
Section: Epigenetic Mechanisms In Memory Formationmentioning
confidence: 99%
“…To construct a robust benchmark dataset, experimentally validated protein sequences with lysine succinylation site details were collected from SwissProt/UniProt (retrieved on 21 May 2017) [17] and Compendium of Protein Lysine Modifications database curated by CUCKOO Workgroup [18]. Initially, 897 proteins with 2523 verified succinylation site (i.e.…”
Section: Datasetsmentioning
confidence: 99%